DEB-TACE with irinotecan versus C-TACE for unresectable intrahepatic cholangiocarcinoma: a prospective clinical study - Wang, Junxiao; Xue, Yaoqin; Liu, Rui; Wen, Zhenyu; Ma, Zhenhu; Yang, Xiang; Yu, Lingxiang; Yang, Bin; Xie, Hui (Frontiers in Bioengineering and Biotechnology, 2023)
Objectives. DEB-TACE with irinotecan and C-TACE were compared with regards to safety and efficacy for the therapy of intrahepatic cholangiocarcinoma (ICC). Methods. Institutional Review Board approved our trial and we registered it in the Chinese Clinical Trial Registry (ChiCTR1900022856). Forty patients with biopsy-confirmed ICC were randomised to either receive DEB-TACE or C-TACE treatment with 20 patients in each treatment arm. The primary endpoints (objective response rate) ORR and (progression free survival) PFS using the mRECIST to evaluate the tumours. The secondary endpoints were OS and safety. The chi-square was used to analyse the data. The Kaplan-Meier method and Cox analysis were used to evaluate the survival data. Results. ORR (70% in DEB-TACE group vs. 20% in C-TACE, P=0.001) at 1 month after therapy, ORR (50% vs. 15%, P=0.018) at 3 months and DCR (70% vs. 30%, P=0.011) at 6 months, while no difference was found in other groups. (all P>0.05) The median PFS with DEB-TACE was longer than that with C-TACE (8.0 months vs 3.0 months) (P=0.042). Although the median OS was longer with DEB-TACE than with C-TACE (11.5 months vs 9.0 months), the difference was not statistically significant (P=0.280). The Cox regression analysis demonstrated that TACE sessions (P=0.017) and low CA125 levels (P=0.001) were independent favourable prognostic factors. The most frequent adverse event was elevated transaminase levels (20/20 in DEB-TACE group vs 15/20 in C-TACE group) (P=0.047). Conclusions. Our prospective study suggested better ORR and PFS with DEB-TACE with irinotecan as compared to C-TACE with Irinotecan in the treatment of unresectable ICC.